2018 IEEE International Conference on Big Data (Big Data) 2018
DOI: 10.1109/bigdata.2018.8622572
|View full text |Cite
|
Sign up to set email alerts
|

Build and Execution Environment (BEE): an Encapsulated Environment Enabling HPC Applications Running Everywhere

Abstract: Variations in High Performance Computing (HPC) system software configurations mean that applications are typically configured and built for specific HPC environments. Building applications can require a significant investment of time and effort for application users and requires application users to have additional technical knowledge. Container technologies like Docker bring great benefits to the application development, build and deployment processes. While much cloud computing infrastructure is already desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…JUBE [14] focuses on running and analyzing benchmarks in a systematic way, with the ability to adapt to the heterogeneous systems through a minimal set of information in XML or YAML-based format. Beeswarm [18] [4] is a solution designed to automate application workflows and integrate with multiple CI providers, based on BEE [3], an autonomous containerization environment and workflow orchestration system. Unlike PCVS, it is not intended for end users but rather for programmatic use in automating the deployment of reproducible applications for validating production developments.…”
Section: Related-workmentioning
confidence: 99%
“…JUBE [14] focuses on running and analyzing benchmarks in a systematic way, with the ability to adapt to the heterogeneous systems through a minimal set of information in XML or YAML-based format. Beeswarm [18] [4] is a solution designed to automate application workflows and integrate with multiple CI providers, based on BEE [3], an autonomous containerization environment and workflow orchestration system. Unlike PCVS, it is not intended for end users but rather for programmatic use in automating the deployment of reproducible applications for validating production developments.…”
Section: Related-workmentioning
confidence: 99%
“…The authors of Build and Execution Environment BEE in [5] propose an execution framework which can, besides others, also deploy Charliecloud container on a HPC infrastructure. Their approach focuses on a variety of different cloud and cluster environments managed by the same authority.…”
Section: Beementioning
confidence: 99%
“…As containers on a host share the underlying operating system kernel, container migration is much more lightweight than a VM migration. Previous works have shown the effectiveness of said tiering approach (i.e., running containers within VM instances) in terms of performance [37], and as a first solution with which to implement fault-tolerance mechanism to run the applications on spot VMs [24]. Moreover, in [38][39][40] it is shown that migration of containers running various real applications is accomplished within a few tens of seconds at most.…”
Section: Achieving Computational Reliabilitymentioning
confidence: 99%